The Relationship between Parenting Style and Dental Anxiety in 4-6 Years Old Children - Fatemeh Haghshenas Gorgabi; Shahrzad Javadinejad; Elham Babaei (Isfahan University of Medical Sciences, 2022)
Control on children`s dental anxiety is one of the important & effective factor predicting treatment success. Personality factors & parenting style can be very effective in children`s dental anxiety. The aim of this study was to determine the relationshipbetween parenting styles and child`s dental anxiety and behavior in dental setting.Materials&Methods:This is a descriptive study done a sample of 126 children aged 4-6 years old and their parents participated in this study in the year 2020. Samplingmethod was non-random and simple. MCDASf questionnaire was used to measure children`s dental anxiety and Bumrind questionnaire was used for scores of parenting styles. Data were analyzed by Pearson Correlation, Spearman Correlation, and chi-square tests.Results:A significant relationship between the score of authoritative parenting style in parents and pediatric dental anxiety (p value = 0.803, r = 0.022). However, a significant inverse relationship was observed between the score of authoritarian parenting style in parents and children's dental anxiety (p value < 0.001, r = -0.307). Also, a direct and significant relationship was observed between the score of permissive parenting style in parents and children's dental anxiety (p value < 0.001, r = 0.318).Conclusion:Dental anxiety and behavior in children is associated with parenting style.